HUBUNGAN RINOSINUSITIS DENGAN SERANGAN ASMA PADA ANAK - , Rr.Vetri Sekar Damayanti, dr, dr. Roni Naning, SpA., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Relationship between asthma and rinosinusitis has been showed in some literatures. More than 50% patients with sinus disease also suffered from asthma. Sinus disease can worsen asthma and mempersulit the management. Sinus disease also has been stated as independent factor for severe and frequent asthma exacerbation. This condition showed that sinonasal involvement might be the risk factor for intensity and frequency of asthma attack This study was aimed to find out the relationship between rinosinusitis and asthma attack in children This study was conducted with cross sectional method to children aged 1- 15 years old. Ninety two subjects, 57 (62,0%) male dan 35 (38,0%) female with asthma attack who fulfill the inclusion and exclusion criteria were enrolled in this study. Assessment and management of asthma attack was based on pedoman Nasional Asma Anak. Subjects then underwent anamnesis, physical examination and plain foto of paranasal sinus to establish rinosinusitis condition. Oddds ratio and 95% confidence interval was calculated for relationship between rinosinusitis and intensity and episodes of asthma attack. Logistic regresion with binary logistic was used for statistical analysis to determine the relationship between rhinosinusitis and episode and degree of asthma attack. From calculation of estimation coefficient or odds ratio (similar to odds ratio in cohort), the OR of rhinnosinusitis and asthma episode was 1,699 (95% CI = 0,661-4,367, p = 0,272). This result showed that p value was > 0,05 and 95% CI was passing the number 1, so it can be concluded that rhinosinusitis was not related to asthma episode statistically. The OR of rhinosinusitis and degree of asthma attack was 7,958 (95% CI = 3,979-16,376, p= 0,019). This result showed that rhinosinusitis related to degree of asthma attack statistically. Rhinosinusitis was not related to asthma episode but related to degree of asthma attack in children 1-15 years old.